The place of Human Rights in teacher training in Social Sciences in Bogotá, Colombia - Agudelo Colorado, Elkin Darío (2023)
This paper presents the results of a research process conducted with teacher training programs in social sciences at the Pedagógica Nacional and Distrital Universities of Bogotá. This study mainly aims to describe and analyze the importance that students and teachers, as key players in the educational process, attribute to the approach of Human Rights during their training and in their professional practice in primary and secondary education. For this purpose, the fundamental bases were the experiences, perceptions, and evaluations of the individuals who are part of these programs.